Pengaruh Citra Merek dan Kualitas Produk terhadap Keputusan Pembelian Kosmetik Maybelline pada Mahasiswi Fakultas Ekonomi Universitas Sriwijaya Palembang - Adristi Lingga Savitri, Shafira; Ahmad Maulana; Aslamia Rosa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determined the influence of brand image and product quality on the purchasing decisions for Maybelline cosmetics on female students of the Faculty of Economics at Sriwijaya University in Palembang. This study is a quantitative research and data obtained through a questionnaire. The sample in this study amounted to 100 respondents using purposive sampling method. The analysis technique used in this study is multiple linear regression analysis, t-test, and F-test. The results of this study indicate that both brand image and product quality simultaneous have a positive and significant effect on purchasing decisions. Partially, brand image has a positive effect on purchasing decisions, but nonsignificant. Whereas product quality has a positive and significant effect on purchasing decisions.